Implementasi Kairos sebagai Metode Pelatihan untuk Meningkatkan Keterampilan Anak di Panti Asuhan Kasih Bapa - Clauvilia, Ega; Ramadania, Ramadania; Fikri, Muahmmad Nafil; Ananta, Carissa Dwi; Wiraldo, Rizky (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This community service program aims to evaluate the impact of basic skills training, such as time management, marketing management, financial literacy, and entrepreneurship, on children at the Kasih Bapa orphanage. This program is designed to equip children at the Kasih Bapa orphanage with knowledge and practical skills that are relevant to everyday life and the world of work. This research involved 13 children from the Kasih Bapa Orphanage in Arang Limbung village Kubu Raya Regency. The methods used include observation, workshops, participatory action, and simulations. Data was gathered using pretests and posttests to measure increases in understanding and skills before and after training. The evaluation results show a significant increase in children's understanding of time management, marketing management, financial literacy, and entrepreneurship. Apart from that, this program also motivates them to develop their potential in the field of entrepreneurship. This training has proven effective in increasing children's awareness and ability to actively participate in economic and social activities, as well as preparing them to become more independent, competitive, and productive individuals in the future.